PEMBICARAAN RINGKAS PUISI-PUISI SUBAGIO SASTROWARDOYO - Zen Hae (POETIKA, 2013)
h: 0px; "> AbstractThis paper attempts to discuss the return of the most important aspects of poetry Subagio Sastrowardoyo. Atfirst he tried to sit Subagio in modern Indonesian literature map by comparing with predecessor and fellow poet ofhis generation. In this comparison, its difference and important characteristics are found, especially their contributionto today‘s Indonesian that is by reintroducing “poetic essays” (essay poem/essayistic poetry) which had already beengrowing in the treasures of foreign literature. In Subagio‘s type, poetry is seen as an attempt to think the endless, whichfurther underline abstract rather than the sensory which is prosaic rather than poetic. As prosaic poem, Subagio seemsnot merely retelling certain treasures, such as puppetry mythology, but the subversion of the origin story. In other parts,Subagio‘s poetry also shows his character as a strong symbolic poetry and also trying to reformulate the poems in thepoetry (Ars Poetica) as a way to present poetry and irony in his chosen style of writing poems.Keywords: Subagio, essayistic poetry, prose writer, subversion